GEOCHEMISTRY OF THE UNGARAN GEOTHERMAL SYSTEM, CENTRAL JAVA, INDONESIA - , Nguyen Kim Phuong , Heru Hendrayana , Agung Harijoko , Ryuchi It ([Yogyakarta] : HAGI-IAGI-PERHAPI, 2005)
Due to water chemistry analysis, most of thermal waters in Gedongsongo are characterized as diluted bicarbonate waters. This water is presented a mixing process between geothermal water and shallow groundwater. Only water in Kaliulo has a very high Na and Cl concentration (more than 4000ppm) as well as HCO3. Thus, it can be explained that these water flow through marine sediment at depth. Isotopic results confirmed that a similar origin of the geothermal fluids and the meteoric water as well as small oxygen shift due to interaction with country rock. Moreover, it is elucidated that water in Kaliulo represents not only mixing between meteoric water and connate water that trapped into Tertiary marine sediment at depth but also rock/water interaction. Emanometry of Rn, CO2, and Hg are also conclusive in the presence of fracture zone for the migration of geothermal fluid and center zone in the southern flank of the Ungaran geothermal system. The CO2 and Hg data show consistency with suggestion that maybe the centre zone of geothermal system around Gedongsongo area. CO2 data is presented of fault along valley nearby the fumarole.